Analysis of power system communication architectures between substations using IEC 61850 - Das, N.; Islam, Syed (2014)
Interoperability among multi-vendor substations automation devices, is now achievable due to the introduction of IEC 61850 standard, which allows power system communication between substations. This standard does not mandatorily demands for redundancy in any type of substation neither does it mentions a specific type of substation design application. Ethernet based communication protocols for substation automation systems (SASs) are specified in IEC 61850 standard. The standards include Ethernet based process-level connections between switchyards and control rooms. However, their in-service performance is not well known. Moreover, IEC 61850 demands for a communication topology which is zero point failure proof and provides worthy data transmission rates, without pursuing any delays. In order to achieve these norms, Ethernet architectures must be modelled and analysed in detail. The performance of individual architecture must be analysed in terms of their reliability, availability and efficiency of data transfer. This paper presents the reliability and availability using the reliability block diagrams, along with OPNET network real-time simulations, which shows the efficiency of individual architecture along with comparing and synthesizing the most effective communication topology for the SASs.